CD8 response measured by QuantiFERON-TB Gold Plus and tuberculosis disease status. Issue 4 (April 2019) - Lee, Meng-Rui; Chang, Chia-Hao; Chang, Lih-Yu; Chuang, Yu-Chung; Sun, Hsin-Yun; Wang, Jann-Tay; Wang, Jann-Yuan
Highlights: QFT-Plus TB2 tube did not enhance clinical utility by positive or negative values. QFT-Plus CD8 response was incremental among uninfected contacts, LTBI and TB. CD8 response was higher among culture-confirmed TB than histology-confirmed TB. CD8 response as measured by TB2 minus TB1, holds promise as a potential biomarker. Summary: Background: Clinical application of the CD8 response as measured by the newer interferon gamma release assay, QuantiFERON-TB Gold-Plus (QFT-Plus), remains to be investigated. Method: We performed this prospective study and recruited active TB patients, contacts with latent tuberculosis infection (LTBI) and contacts without LTBI in two centres in northern Taiwan in 2017. Subjects were tested with both QuantiFERON-TB Gold In-Tube (QFT-GIT) and QFT-Plus. LTBI was defined by positive result by QFT-GIT and exclusion of active TB. Results: A total of 336 participants (118 uninfected contacts, 105 LTBI, 113 active TB) were included. The concordance rate of QFT-GIT and QFT-Plus was high ( n = 300, 89.3%). The kappa value was 0.811 among contacts and 0.708 among active TB. While TB1 and TB2 quantitative responses were not different between active TB and LTBI (TB1: 1.74 ± 2.73 IU/ml vs. 2.03 ± 2.28 IU/ml, p = 0.403; TB2: 2.21 ± 3.09 IU/ml vs. 2.15 ± 2.40 IU/ml, p = 0.867), CD8 response was higher in active TB than LTBI (0.47 ± 1.53 IU/ml vs. −0.06 ± 1.47 IU/ml, p = 0.011). Culture-confirmed TB had a higher CD8 response compared with LTBI (0.63 ± 1.74 IU/ml vs. −0.05 ± 1.47 IU/ml, p = 0.004). Conclusions: This study demonstrated specific CD8 responses among uninfected contacts, LTBI as well as active TB.